Photo-oxidation of Polypropylene Fiber and Effective Parameters: A Review - Zahra Ahmadi; Mohamad Haghighat Kish (علوم و تکنولوژی پلیمر, 2013)
Production of polypropylene is growing for applications in different types of textiles. The main limitations in some of their applications are attributed to its low photostability and related property changes. There are several factors that have considerable effects on the process of photo-oxidation and the resulting photostability. From polymer production up to its usage the recognition of these parameters is necessary in order to control the degradation and to improve the useful life period of the products. In this paper, first the photo-oxidation mechanism of polypropylene in the presence of air is reviewed and then the effects of different factors including additives are examined. The incorporation of additives and light stabilizers in polymers are important in order to preserve their long-term use in the environment. Besides the complex mechanisms of photostabilization, this review presents an in-depth account of the behavior of the additives with respect to the photochemical oxidation of polypropylene and the interactions involved. Stabilization of polypropylene was improved in the presence of a mixture of photostabilizers, exhibiting an enhanced irradiation resistance. It would appear that the origin and composition of the pigment and its interaction with photostabilizers are all important factors. Several analytical techniques were employed to evaluate the stabilization effectiveness of the additives and degradation process; finally the techniques and the experimental methods for evaluation of photo-oxidation level and photo-oxidation products are introduced. Thedifferences in the views are highlighted and the shortcomings are explained.